Pengaruh Media Interaktif Terhadap Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti kelas XII di SMA N 1 Jatilawang - Wulan Windadinanti, Wulan (Jurnal Pendidikan Agama Islam, 2025)
Learning outcomes are academic achievements achieved by students through assignments and exams, as well as active asking and answering questions that support their learning outcomes. This study explains the importance of interactive media so that classroom learning is interesting and increases student learning motivation and maximum learning outcomes. The interactive media used by researchers is the snakes and ladders game based on the Genially platform, where on this platform there are various features and media that can be used by educators to create interesting media for learning. The purpose of this study was to determine whether or not there is an influence of interactive media and how much influence interactive media has on student learning outcomes in the PAI BP subject of class XII at SMA N 1 Jatilawang. The type of research used is quantitative experimental research with a purposive sampling approach. The results of this study indicate that there is a significant influence on the influence of interactive media on student learning outcomes in the PAI BP subject of class XII at SMAN N 1 Jatilawang both before and after the implementation of interactive media through the results of hypothesis testing that has been carried out. There is a pretest value with an average of 58.33 and a posttest value of 94.25. The results of student responses in the application of interactive media in the PAI BP subject in class XII were found to be mostly in the high category where the percentage was 98.15% indicating that students agreed with the existence of interactive media in the learning and had a positive attitude towards their students' learning outcomes